Answer:
Therefore the length of QP = 3.4 units
Explanation:
Given:
PQ = 2x + 1
XF = 7x - 4
PF = x
Q is the mid poimt of XF
∴ XQ = QF
QF = PQ - PF ..........( Q - F - P )
= 2x + 1 - x
∴ QF = x + 1
∴ XQ = QF = x + 1
TO Find:
QP = ?
Solution:
By Addition Property we have
![XP = XQ + QF+PF ..........(X-Q-F-P)\\\\](https://img.qammunity.org/2020/formulas/mathematics/high-school/6jaiz34z0mqced6rhx2m8wcyrfis17ef21.png)
![XF + PF =XQ + QF+PF ..........(X-Q-F-P)\\](https://img.qammunity.org/2020/formulas/mathematics/high-school/woc2p859ltn8k7z7j9dhsgmmnl0w1rkg2k.png)
Substituting the given values in above equation we get
(7x - 4) + x = (x +1) + (x +1) + x
8x -4 = 3x +2
8x - 3x + 4 + 2
5x = 6
∴
![x = (6)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/otibbhjvict7hwjv769rwqz9ak0hnbjnd9.png)
Now we require
QP = (2x + 1)
∴
![QP = 2* (6)/(5) +1\\\\QP = (12+5)/(5) \\\\QP =(17)/(5) \\\\\therefore QP = 3.4\ unit](https://img.qammunity.org/2020/formulas/mathematics/high-school/kdo15ag6ogv8qhck2c2a7tdg51hfkryfjk.png)
Therefore the length of QP = 3.4 units